# 42 - Many solutions

For an overview of this madness, see http://www.bbc.co.uk/h2g2/guide/A530560

It is usually pretty easy to make your researcher number add/subtract/divide/multiply to 42 without resorting to 'higher' mathematical functions such as sine, exponential, etc. I was able to find one solution pretty quickly, but here are 56 of them, using only basic mathematical operators.

(note - I haven't properly checked all of these but I reckon they're all unique)

(from 174602)

((((+1)+7)+4)+(60/2)) = 42
(((+1)-7)+(((4*6)+0)*2)) = 42
(((+1)-7)+(((4*6)-0)*2)) = 42
(((+1)-7)+((4*6)*(0+2))) = 42
((+1)-(7+((4*6)*(0-2)))) = 42
(((+1)-7)+((4*6)*02)) = 42
(((((+1)-7)+46)+0)+2) = 42
((((+1)-7)+46)+02) = 42
(((((+1)-7)+46)-0)+2) = 42
((((+1)-7)+46)-(0-2)) = 42
((+1)-(7-(((4*6)+0)*2))) = 42
((+1)-(7-(((4*6)-0)*2))) = 42
((+1)-(7-((4*6)*(0+2)))) = 42
(((+1)-7)-((4*6)*(0-2))) = 42
((+1)-(7-((4*6)*02))) = 42
((((+1)-(7-46))+0)+2) = 42
((+1)-(((7-46)+0)-2)) = 42
(((+1)-(7-46))+02) = 42
((((+1)-(7-46))-0)+2) = 42
(((+1)-(7-46))-(0-2)) = 42
((+1)-((7-46)-02)) = 42
((((+1)-(7*4))+6)*(0-2)) = 42
(((+1)-((7*4)-6))*(0-2)) = 42
(((+1)*7)*((4+(6*0))+2)) = 42
(((+1)*7)*((4-(6*0))+2)) = 42
(((+1)*7)*(4-((6*0)-2))) = 42
((((+17)+4)+(6*0))*2) = 42
((((+17)+4)-(6*0))*2) = 42
(((+17)+4)*((6*0)+2)) = 42
(((-1)+7)*(4+((6+0)/2))) = 42
(((-1)+7)*(4+((6-0)/2))) = 42
(((-1)+7)*(4+(6/(0+2)))) = 42
(((-1)+7)*(4+(6/02))) = 42
(((((-1)+7)*4)+60)/2) = 42
(((((-1)+(7*4))-6)+0)*2) = 42
(((((-1)+(7*4))-6)-0)*2) = 42
((((-1)+(7*4))-6)*(0+2)) = 42
((((-1)+(7*4))-6)*02) = 42
(((-1)+7)*(4-(6/(0-2)))) = 42
(((-((1-(7*4))+6))+0)*2) = 42
((-(1-7))*(4+((6+0)/2))) = 42
(((-((1-(7*4))+6))-0)*2) = 42
((-(1-7))*(4+((6-0)/2))) = 42
((-((1-(7*4))+6))*(0+2)) = 42
((-((1-(7*4))+6))*02) = 42
((-(1-7))*(4+(6/(0+2)))) = 42
((-(1-7))*(4+(6/02))) = 42
((((-(1-7))*4)+60)/2) = 42
((((-(1-(7*4)))-6)+0)*2) = 42
((((-(1-(7*4)))-6)-0)*2) = 42
(((-(1-(7*4)))-6)*(0+2)) = 42
(((-(1-(7*4)))-6)*02) = 42
((-(1-7))*(4-(6/(0-2)))) = 42
((-(((1-7)*4)-60))/2) = 42
((-(17+4))*((6*0)-2)) = 42
(((-17)-4)*((6*0)-2)) = 42